1991
DOI: 10.1111/j.1471-0528.1991.tb13369.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide and atrial size during normal pregnancy

Abstract: Summary. Plasma atrial natriuretic peptide (ANP), right and left atrial areas and the diameter of the left atrium were studied serially during normal pregnancy and at 6 weeks post partum in 21 nulliparous women. Concentrations of ANP in plasma were significantly elevated during mid‐pregnancy. Thereafter ANP levels were not significantly different from those at 6 weeks after delivery. All atrial measurements were significantly increased in the third trimester of pregnancy, but none was significantly correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 36 publications
(26 reference statements)
3
4
0
Order By: Relevance
“…Our results indicate that ANF levels are elevated by day 7 of normal rat pregnancy; in no other studies have ANF levels been measured this early in pregnancy. Our finding that plasma ANF levels return to non-pregnant values near term is in agreement with previous data from rats (Castro et al 1989) and humans (Otsuki et al 1987;Steegers et al 1991), but is nonetheless surprising since circulating blood volume is greatly expanded at this time (Barron, 1987) and is associated with significant atrial distension, at least in humans (Steegers et al 1991). It is generally agreed that postpartum levels of ANF are significantly elevated in both the human and the rat (Nadel et al 1988;Castro et al 1989;Jansakul et al 1989;Marlettini et al 1989); our data are in agreement with these findings.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results indicate that ANF levels are elevated by day 7 of normal rat pregnancy; in no other studies have ANF levels been measured this early in pregnancy. Our finding that plasma ANF levels return to non-pregnant values near term is in agreement with previous data from rats (Castro et al 1989) and humans (Otsuki et al 1987;Steegers et al 1991), but is nonetheless surprising since circulating blood volume is greatly expanded at this time (Barron, 1987) and is associated with significant atrial distension, at least in humans (Steegers et al 1991). It is generally agreed that postpartum levels of ANF are significantly elevated in both the human and the rat (Nadel et al 1988;Castro et al 1989;Jansakul et al 1989;Marlettini et al 1989); our data are in agreement with these findings.…”
Section: Discussionsupporting
confidence: 94%
“…By the third week of pregnancy in the rat, basal plasma ANF levels were no longer elevated, and the lack of response to atrial distension was maintained. Several possibilities have been put forward to explain the failure of plasma ANF to rise in late pregnancy despite the increase in circulating blood volume (Barron, 1987) and the echocardiographic evidence for atrial distension (Steegers et al 1991). It has been suggested that elevated ANF secretion in late pregnancy might be balanced by an increased rate of clearance, so that circulating levels are unchanged (Nadel et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Reports from other laboratories have suggested that the normal pregnancy showed a decline in circulating ANP levels, or levels in the third trimester similar to those in non-pregnant controls [8,27,31,39]. Oguni et al [31] suggested that these different results in the third trimester of normal pregnancy depended on the methodological conditions, especially in the specific antibody in radioimmunoassay.…”
Section: Discussionmentioning
confidence: 99%
“…Nadel et al [27] proposed that the lack of rise in circulating ANP levels during pregnancy was explained by some reasons whereby the increased intravascular volume was not sensed by the atrial volume receptors, because the size of the maternal vascular compartment was similarly increased, or in which the chronic extracellular volume expansion did not result in elevated levels of ANP. A different explanation for ANP levels failing to be continuously elevated in association with long-term hypervolemia can be attributed to that atrial volume receptors are reset or have a decreased sensitivity during chronic atrial dilatation [39]. The decrease in the plasma ANP level in the third trimester was suggested to be due to an increase in circulating blood volume compensated by a simultaneous increase in the vascular capacity, namely, a reduction in systemic vascular resistance in normal pregnancy, thus imposing no extra preload on the heart.…”
Section: Discussionmentioning
confidence: 99%
“…This has been due to problems with study design (cross sectional) and methodo-logical¯aws such as inadequate inhibition of circulating placental peptidases as well as the assay of unextracted or stored plasma samples. 49 Voto et al during validation work doubled inhibitor concentration in the sampling tubes prior to centrifugation, which improved recovery when comparing fetal with maternal plasmas. 9 For instance, Nisell et al maintained that enzyme inhibitors were unnecessary 48 and Steegers et al during their early work added enzyme inhibitors after blood had been centrifuged.…”
Section: Human Pregnancymentioning
confidence: 99%